Pancreatitis Quality of Life Instrument: A Psychometric Evaluation. (August 2016) - Wassef, Wahid; DeWitt, John; McGreevy, Kathleen; Wilcox, Mel; Whitcomb, David; Yadav, Dhiraj; Amann, Stephen; Mishra, Girish; Alkaade, Samer; Romagnuolo, Joseph; Stevens, Tyler; Vargo, John; et al.
Abstract : OBJECTIVES: Chronic pancreatitis is a significant medical problem that impacts a large number of patients worldwide. In 2014, we developed a disease‐specific instrument for the evaluation of quality of life in this group of patients: pancreatitis quality of life instrument (PANQOLI). The goal of this study was to evaluate its psychometric properties: its reliability and its construct validity. METHODS: This is a cross‐sectional multi‐center study that involved 12 pancreatic disease centers. Patients who met the inclusion/exclusion criteria for chronic pancreatitis were invited to participate. Those who accepted were asked to complete seven questionnaires/instruments. Only patients who completed the PANQOLI were included in the study. Its reliability and its construct validity were tested. RESULTS: A total of 159 patients completed the PANQOLI and were included in the study. They had a mean age of 49.03, 49% were male, and 84% were Caucasian. Six of the 24 items on the scale were removed because of lack of inter‐item correlation, redundancy, or lack of correlation to quality of life issues. The final 18‐item scale had excellent reliability (Cronbach's alpha coefficient: 0.914) and excellent construct validity with good correlation to generic quality of life instruments (SF‐12 and EORTC QLQ‐C30/QLQ‐PAN26) and lack of correlation to non‐quality of life instruments (MAST and DAST). Through exploratory factor analysis, the PANQOLI was found to consist of four subscales: emotional function scale, role function scale, physical function scale, and "self‐worth" scale. CONCLUSIONS: PANQOLI is the first disease‐specific instrument to be developed and validated for the evaluation of quality of life in chronic pancreatitis patients. It has a unique subscale for "self‐worth" that differentiates it from other generic instruments. Studies are currently under way to evaluate its use in other populations not included in this study.